Carbohydrate for endurance athletes in competition : assessing knowledge and nutritional practices - Sampson, G. (Liverpool John Moores University, 2020)
A key role of a practicing sports dietitian working with competitive endurance athletes is to translate complex information, educate and support athletes to make nutritional changes to their dietary behaviour for improved performance outcomes. Current carbohydrate (CHO) guidelines based upon a wealth of literature demonstrate clear performance benefits when endurance athletes compete with optimal CHO availability. Despite this strong scientific evidence and sports nutrition guidelines recommending CHO intakes to enhance endurance sports performance, a clear mismatch still exists between current guidelines and practice amongst endurance athletes as evidenced in the Literature Review (Chapter 2). With this in mind, the aim of this Professional Doctorate thesis was to investigate whether athletes fail to consume optimal CHO in competition because they were unaware and lack knowledge of the current CHO guidelines, have difficulties with translating knowledge into practice, have personal beliefs or are exposed to external factors which influence their dietary intake within competition. To systematically assess CHO knowledge, we first needed to develop a tool and methodology to do so. Thus, the aim of Study 1 (Chapter 3) was to develop and validate a CHO specific nutrition knowledge assessment tool, based upon contemporary carbohydrate guidelines. The Carbohydrate for Endurance Athletes in Competition Questionnaire (CEAC-Q) consists of 25 questions divided into 5 subsections: CHO metabolism, loading, pre-race meal, during race and recovery with each subsection worth 20 points resulting in a total maximum possible score of 100. A between-groups analysis of variance assessed construct validity between the general population (GenP; n = 67), endurance athletes (EA; n = 145), and registered sports dietitians/nutritionists (SDN; n = 60) with expected increasing levels of knowledge respectively. As expected, there was increasing level of knowledge between populations with a significant difference in CEAC-Q total and subsection scores (mean ±SD) observed between all pairwise comparisons; GenP (17 ±20 %, 3 ±5), EA (46 ±19 %, 9 ±5) and SDN (76 ±10 %, p = < 0.001, 15 ±4 %, p = 0.001), respectively. The CEAC-Q took athletes an average 10:36 ±07:45 minutes to complete online. These data demonstrate that CEAC-Q is a new psychometrically valid, practical and time-efficient tool for practitioners to assess athletes' 2 knowledge of CHO for competition in less than 10 minutes, allowing for quick and accurate identification of knowledge gaps to nutrition strategies to optimise performance. Having developed a suitable CHO knowledge assessment tool in Study 1 (Chapter 3), the aim of Study 2 (Chapter 4) was to assess current knowledge levels and identify knowledge gaps on an international cohort of EA. The CEAC-Q was completed online by EA (n = 1016) actively competing in endurance sporting events (cycling, triathlon and running) with mean CEAC-Q total and subsection scores of 50 ±20% and 10 ±5, respectively. Multiple regression determined that years of competitive experience, competitive level and a sports nutritionist influence were positively related to CEAC-Q scores. Clear knowledge gaps transpired where correct knowledge of current CHO guidelines was shown by 28% (n = 284) for CHO loading, 45% (n = 457) for the pre-competition meal, 48% (n = 487) for during competition lasting >2.5 h and 29% (n = 296) for post-competition recovery. The CEAC-Q identified common gaps in knowledge of CHO guidelines that require further education that may partially explain why athletes fail to meet them within competition. Since Study 2 (Chapter 4) identified clear knowledge gaps of current CHO guidelines, the aim of Study 3 (Chapter 5) was to assess the relationship between knowledge of CHO guidelines and dietary intake within athletes competing in real-world competition. Amateur and elite athletes (n = 50) competing in international cycling, triathlon and marathon events recorded dietary intake for the 24 h period before competition (CHO loading) and pre-competition meal using Remote Food Photography Method, with intake during collected by recall immediately after competition. Intake was compared against the CEAC-Q scores and knowledge of current guidelines. Correct knowledge of current guidelines was shown by 36% (n = 18) of athletes for pre competition day CHO loading and 64% (n = 32) for CHO intake during events. In relation to practice, 84 % (n = 42) athletes failed to achieve pre-competition day CHO intake guidelines by ingesting 6.5 ±2.2 g•kg-1 and 68% (n = 34) failed to achieve CHO intake during competition guidelines by ingesting 52 ±2 g•h-1. No association was evident between knowledge of CHO guidelines and dietary intake for CHO loading, the pre-event meal or during competition. Knowledge may be a facilitator, but it seems evident that actual dietary choices within competition are strongly influenced by factors other than theoretical knowledge. Abstract 3 Abstract Given that Study 3 (Chapter 5) observed endurance athletes who identified CHO guidelines did not consistently translate this knowledge into practice, Study 4 (Chapter 6) aimed to explore factors explaining the lack of association between knowledge of CHO guidelines and actual CHO loading and during competition intakes. Semi-structured interviews were conducted 7 - 14 days post-competition in the same 50 amateur and professional endurance athletes from Study 3 (Chapter 5). Interview transcripts were first analysed inductively line- by-line using reflexive thematic analysis. A deductive approach then applied the COM-B model of behaviour change as a coding framework to inform a position of all factors influencing the capability, opportunity and motivation of endurance athletes to apply knowledge to dietary practice 24 h before and during competition. Endurance athletes did not achieve CHO loading guidelines due to low knowledge and skills (capability), or personal beliefs and fears that limited their motivation to increase CHO intake. Conversely, despite knowing CHO guidelines during competition, athletes were frequently exposed to external factors (weather, intensity, regulations) during competition that limited the opportunity to consume planned CHO intake. Having identified key limiting factors between knowledge and practice, these can be suitably addressed via targeted nutrition education, interventions and behaviour change techniques. In summary the data presented in this thesis demonstrate that the CEAC-Q is a time-efficient tool that sports dietitians can use collectively with dietary records and motivational interviewing (nutritional counselling) to identify gaps in knowledge, beliefs and external factors that influence why athletes fail to achieve recommended CHO within competition. These can subsequently guide appropriate education and dietary interventions using the most appropriate behaviour change techniques that enhance the relevant capability, opportunity or motivation for athletes to change their CHO intake to better align with CHO guidelines for competition.